Islam di Sicilia: Asal-usul, Kemajuan dan Kehancuran - Munawir, M. Fajrul (UIN Maulana Malik Ibrahim Malang, 2009)
Islam authority in Sicilia was being parts of history of Islamic civilization in Europe. The aim of this article is tried to explain background, progression and decline of Islam in Sicilia. Glory of Islam in Sicilia had started in Bani Aghlab period. Bani Aghlab period had already been shaping the important civilization of spreading Islam in Europe 184 H/800 M. Sicilia become center of science and Islamic culture in Europe. Great Land is epithet of prosperity in Sicilia. Decline of Sicilia had appeared when reformation authority from Aghlabiyah to Fatimiyah. Christian Romawi succeeded dominate Sicilia in 871 M until 1090 M. Finally, Sicilia had been formed golden history and spreading Islamic civilization in Europe. Islam authority in Sicilia was being parts of history of Islamic civilization in Europe. The aim of this article is to explain background, progression and decline of Islam in Sicilia. Glory of Islam in Sicilia had started in Bani Aghlab period. Bani Aghlab period had already been shaping the important civilization of spreading Islam in Europe 184 H/800 M. Sicilia become center of science and Islamic culture in Europe. Great Land is epithet of prosperity in Sicilia. Decline of Sicilia had appeared when reformation authority from Aghlabiyah to Fatimiyah. Christian Romawi succeeded to dominate Sicilia in 871 M until 1090 M. Finally, Sicilia had been formed golden history and spreading Islamic civilization in Europe.